1999
DOI: 10.1046/j.1365-2583.1999.00145.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in geographical populations of western and Mexican corn rootworm

Abstract: Genetic variation in the nuclear rDNA ITS1 region of western corn rootworm, Diabrotica virgifera virgifera (WCR), and Mexican corn rootworm, D. v. zeae (MCR) was studied. Two sites were detected which differentiated WCR and MCR in the 642-base sequence. Polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) analysis of the first internal transcribed spacer region (ITS1) sequence revealed no variation within or among the twelve WCR and two MCR populations. PCR-RFLP of 75% of the mitochond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 29 publications
2
25
0
Order By: Relevance
“…Western corn rootworm in the United States has very little genetic polymorphism across its geographic distribution (Szalanski et al 1999). By contrast, northern corn rootworm is genetically diverse with polymorphism both at the local population level and on a broader geographic scale.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Western corn rootworm in the United States has very little genetic polymorphism across its geographic distribution (Szalanski et al 1999). By contrast, northern corn rootworm is genetically diverse with polymorphism both at the local population level and on a broader geographic scale.…”
Section: Resultsmentioning
confidence: 99%
“…To check whether the primers reacted differently depending on the geographic origin of the template, the primer combinations were tested with DNA from adults and larvae of 20 western corn rootworms from South Dakota, North Dakota, and Indiana and adults of 38 northern corn rootworms from North Dakota, South Dakota, Wisconsin, Iowa, Pennsylvania, and Þve sites in Illinois. The western corn rootworms were from locations previously shown to have extremely low mtDNA polymorphism (Szalanski et al 1999). The northern corn rootworm samples are from both sides of a major population genetic boundary located in Illinois (unpublished).…”
Section: Resultsmentioning
confidence: 99%
“…However, the use of the colonies introduces two possible confounding factors into the analysis, namely: a possible geographic effect and a possible artifact attributable to selection in a closed colony. While these possibilities must be acknowledged, several molecular studies of genetic diversity have shown that there is little or no geographic structuring in Diabrotica (Szalanski et al, 1999;Kim and Sappington, 2005) and no significant differences in genetic diversity between insects from the laboratory colonies at the North Central Agricultural Research Table 1 Western corn rootworm mean foraging transcript number at three stages of development (Fig. 4) Laboratory in Brookings, SD (which have been maintained for more than 20 generations) and insects collected from the wild (Kim et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Because the boll weevil is a recent colonist of the United States, a relatively low level of genetic variation caused by founder effects is to be expected (Szalanski et al 1999, Roehrdanz 2001, and both allozyme and mtDNA RFLP data are consistent with this supposition (Terranova et al 1990, Roehrdanz 2001. In this study, the use of a long fragment of mtDNA and screening with a large number of restriction enzymes made it possible to identify enough RFLPs to analyze population genetic structuring in this insect despite its history of recent colonization.…”
Section: Discussionmentioning
confidence: 99%